Response of the mollusc communities to environmental factors along an anthropogenic salinity gradient - Agnieszka Sowa; Mariola Krodkiewska; Dariusz Halabowski; Iga Lewin (The Science of Nature, 2019)
Anthropogenic salinisation of freshwater ecosystems is frequent across the world. The scale of this phenomenon remains unrecognised, and therefore, monitoring and management of such ecosystems is very important. We conducted a study on the mollusc communities in inland anthropogenic ponds covering a large gradient of salinity located in an area of underground coal mining activity. A total of 14 gastropod and 6 bivalve species were noted. No molluscs were found in waters with total dissolved solids (TDS) higher than 17.1 g L −1 . The share of alien species in the communities was very high in waters with elevated salinity and significantly lower in the freshwaters. Canonical correspondence analysis (CCA) showed that TDS, pH, alkalinity, nitrate nitrogen, ammonium nitrogen, iron, the content of organic matter in sediments, the type of substrate and the content of sand and gravel in sediments were the variables that were significantly associated with the distribution of molluscs. The regression analysis revealed that total mollusc density was positively related to alkalinity and negatively related to nitrate nitrogen. The taxa richness was negatively related to TDS, which is consistent with previous studies which indicated that a high salinity level is a significant threat to freshwater malacofauna, causing a loss of biodiversity and contributing to the colonisation and establishment of alien species in aquatic ecosystems.